KARAKTERISASI MEKANIK BIOKOMPOSIT KLOBOT JAGUNG SEBAGAI BAHAN DASAR PLASTIK BIODEGRADABLE - Dirgantara, Made; Saputra, Miko; Khalid, Muhammad; Wahyuni, Eni Septi; Kurniati, Mersi (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
The corn production in Indonesia, based on the data from Badan Pusat Statistik in 2012, amounted to 19.73 million tons, the cornhusk from the corn crop is about 38.38%. The utilization of cornhusk itself has not been maximized yet, so the research to maximize the utilization of cornhusk is required. The research has been made biocomposites cornhusk and Linear Low Density Polyethylene (LLDPE) with hot press method. Biocomposites made with the variation of cornhusk:LLDPE are 30:70, 40:60, 50:50, 60:40, 70:30, and it is characterized of the mechanical characteristics (tensile and tear) with Universal Testing Machine (UTM), biodegradation in a qualitative manner. Mechanical analysis showed the mechanical characteristics decrease with the addition of cornhusk concentration on biocomposites, and concentration 30:70 has the highest mechanical characteristics with tensile strength 24.77 MPa, elongation 19.10% and tear strength 53.94 N/mm. The result is contrast with the biodegradable analysis in which the bigger concentration cornhusk then the level of biodegradability is higher.Keywords: biocomposites, biodegradable,Â cornhusk, mechanical characteristic